1993
DOI: 10.1007/bf00046752
|View full text |Cite
|
Sign up to set email alerts
|

Proton release during the redox cycle of the water oxidase

Abstract: Old and very recent experiments on the extent and the rate of proton release during the four reaction steps of photosynthetic water oxidation are reviewed. Proton release is discussed in terms of three main sources, namely the chemical production upon electron abstraction from water, protolytic reactions of Mn-ligands (e.g. oxo-bridges), and electrostatic response of neighboring amino acids. The extent of proton release differs between the four oxidation steps and greatly varies as a function of pH both, but d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
126
0
6

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(147 citation statements)
references
References 83 publications
15
126
0
6
Order By: Relevance
“…During the S 2 →S 3 transition, the substrate water molecule bound to Mn(4) is deprotonated, consistently with electrochromism data (Haumann & Junge 1996;Junge et al 2002;Lavergne & Junge 1993;Schlodder & Witt 1999;Witt 1996), and the oxidation state of Mn(4) is advanced from III to IV. These changes induce inter-ligand proton transfer from the HO -ligand of Mn (3) to the hydrogen bonded HO -ligand of Mn(4), strengthening the attractive interactions between Mn(4) and the HO -ligand of Mn(3), forming a μ-oxo bridge between Mn(3) and Mn (4), and transforming the HO -ligand of Mn(4) into a water ligand (the HO -proton acceptor is regenerated by deprotonation of the water ligand in the S 0 →S 1 transition).…”
Section: Qm/mm Mechanistic Model Of Water Splittingsupporting
confidence: 74%
“…During the S 2 →S 3 transition, the substrate water molecule bound to Mn(4) is deprotonated, consistently with electrochromism data (Haumann & Junge 1996;Junge et al 2002;Lavergne & Junge 1993;Schlodder & Witt 1999;Witt 1996), and the oxidation state of Mn(4) is advanced from III to IV. These changes induce inter-ligand proton transfer from the HO -ligand of Mn (3) to the hydrogen bonded HO -ligand of Mn(4), strengthening the attractive interactions between Mn(4) and the HO -ligand of Mn(3), forming a μ-oxo bridge between Mn(3) and Mn (4), and transforming the HO -ligand of Mn(4) into a water ligand (the HO -proton acceptor is regenerated by deprotonation of the water ligand in the S 0 →S 1 transition).…”
Section: Qm/mm Mechanistic Model Of Water Splittingsupporting
confidence: 74%
“…In this study we compared both the extent and the kinetics of proton release, electrochromism and electron transfer in thylakoids and core particles. Only these materials are suitable for high time resolution of proton release [2]. We found no correlation between the net charge as based on proton release and the extent of the electrochromic transients.…”
Section: Intraductionmentioning
confidence: 57%
“…To overcome this complication we used the variability of the rate of proton release as a kinetic label for those events which are coupled to proton release. The rate of proton release can be speeded up (i) in thylakoids by increasing the concentration of Neutral red or of imidazole, both reacting as mobile buffers by direct collision with the proton donating groups, and (ii) in core particles at acid pH where the deprotonation is due to protolysis and is rapid due to the dominance of groups with a more acid pK (see [2]). Electron transfer, electrochromism and proton release were time resolved at pH 7.4 in thylakoids and pH 5.5 in core particles on the first four flashes in dark adapted material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Chu et al [28, Mn, it is thought to play a structural role by inducing the correct geometry of the Mn-binding sites (see [9]). Recent experiments have shown that the presence of Ca2+ inhibits the labilization of OEC Mn reduced by hydroxylamine [32, 331. Finally, proton motion during the water oxidation process (reviewed in [34]) is likely to be crucial for proper function of the water-splitting process [13], and amino acid side chains undoubtedly play a central role in facilitating the egress of protons from the oxidizing side of the photosystem. The results of Chu et al [30] suggest that His-I90 of the D1 polypeptide may be involved in this function.…”
Section: Introductionmentioning
confidence: 99%